Preparation of Expandable Graphite with Phosphoric Acid as Ancillary Intercalation Reagent and its Antiflame Property for Linear Low Density Polyethylene - Pang, Xiu-Yan; Duan, Ming-Wei; Tian, Yu; Zhai, Meng (Asian Journal of Chemistry, 2013)
To prepare graphite intercalation compound-expandable graphite (EG) with well antiflame property for linear low density polyethylene (LLDPE), dosages of oxidant KMnO4, intercalation reagent H2SO4 and ancillary intercalation reagent H3PO4 were optimized during chemical oxidation intercalation reaction of natural graphite. Expandable graphite with an initiation expansion temperature of 160 ºC and expansion volume of 430 mL/g can be prepared according to the mass ratio C:KMnO4:H2SO4 (98 %):H3PO4 (85 %) of 1.0:0.2:3.0:0.3 (H2SO4 should be diluted to the mass concentration of 75 % before intercalation reaction), the reaction lasts 1 h at 40 ºC. Addition of 30 % of the prepared expandable graphite to linear low density polyethylene can improve its limiting oxygen index (LOI) from 17.3 % to 25.7 % and the synergistic antiflame limiting oxygen index of 20 % expandable graphite with 10 % ammonium polyphosphate (II) (APP II) can reach to 27 %. Thermal gravimetric and differential thermal analysis were completed to discuss the antiflame mechanism. 70 % LLDPE/10 % APP(II)/20 % EG synergistic antiflame system can cause higher residual carbon and lower material surface temperature.